An introduction to the world of microbes - Westenberg, David (Henry Stewart Talks, 2019)
The high diversity and pervasiveness of microbes, History of microbiology, Observing microbes and the advancement of microscopy, Describing and distinguishing microbes, Microbes in health and disease, Microbes, evolution, and the environment, Putting microbes to work: microbes and food & synthetic biology